Hymenoptera reared from Plagiotrochus suberi (Hymenoptera: Cynipidae) galls in California - Zuparko, R L (Pan-Pacific Entomologist, 1996)
Nine species of Hymenoptera were reared from stem galls induced by Plagiotrochus suberi Weld on Quercus suber L. in Albany, California. The most numerous species reared was P. suberi, but Euderus crawfordi Peck was the most common parasitoid reared. Other species reared were: Aprostocetus pattersonae (Fullaway), A. sp. nr. verrucarii (Balduf), Acaenacis taciti (Girault), Sycophila wiltzae(Balduf), Sycophila sp, possibly foliatae (Ashmead), Brasema sp. and Ceraphron sp. The rearings of all parasitoids (except E. crawfordi and S. wiltzae) constitute new host records. All described parasitoid species are native to North America and represent new associations with the introduced P. suberi.
Keywords: associations; Euderus crawfordi; Insecta; new; Parasitoids; Plagiotrochus suberi; Pragas e doenças do sobreiro - Plagiotrochus suber; Quercus suber